2015
DOI: 10.1007/s11356-015-4385-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiwalled carbon nanotubes on UASB microbial consortium

Abstract: The continuous rise in production and applications of carbon nanotubes (CNTs) has grown a concern about their fate and toxicity in the environment. After use, these nanomaterials pass through sewage and accumulate in wastewater treatment plants. Since, such plants rely on biological degradation of wastes; their activity may decrease due to the presence of CNTs. This study investigated the effect of multiwalled carbon nanotubes (MWCNTs) on upflow anaerobic sludge blanket (UASB) microbial activity. The toxic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In addition, Yadav et al . () correlated the cell damage (on UASB microbial flocs) caused by CNT with the increase of extracellular polymeric substances production. However, in the present study, the amount of extracellular substances seems to decrease with increasing concentrations of CNT (Figs and 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Yadav et al . () correlated the cell damage (on UASB microbial flocs) caused by CNT with the increase of extracellular polymeric substances production. However, in the present study, the amount of extracellular substances seems to decrease with increasing concentrations of CNT (Figs and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Toxic effects of CNT have also been reported. These materials may affect microbial community diversity and reduce the number of actively growing bacteria (Kang et al ., ; Pasquini et al ., ; Mohanty et al ., ; Yadav et al ., ). In addition, Yadav et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its integration into various sectors, including pharmaceutical, energy, agriculture, construction, and wastewater treatment (Yadav et al 2016, Casals et al 2014, has raised concerns with respect to the environmental safety; most investigations focus on the potential effects on human health and the environment (Helland et al 2008, Petersen et al 2011. Some studies have reported the toxic effects of carbon nanotubes (Yadav et al 2016, Mwangi et al 2012, Simon-Deckers et al 2009) and zinc oxide nanoparticles (Mu et al 2012) on microorganisms, cells, and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [111] followed up on the degradation of sucrose with 0 or 1000 mg/L of SWNT for 174 h, and indicated that faster substrate consumption and higher amount of methane took place when the nanotubes were added. Yadav et al [112] incubated the sludge with 0, 1 and 100 mg/L of MWNT for 15 days, and noticed that the higher the nanomaterial concentration, the lower the microbial growth, the cell membrane integrity, the amount of volatile fatty acids generated and the biogas volume.…”
Section: Anaerobic Treatment Of the Sludgementioning
confidence: 99%